Center-Pivot-Irrigated Forage Sorghum Silage Cost-Return Budget - O'Brien, Daniel M.; Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2002)
This publication estimates the costs and returns associated with center-pivot-irrigated forage sorghum put up as silage in western Kansas.
MF998_2002_10
Keywords: MF998; Economics; Crops; MF